Satellite-Based Detection of Floating Plastic Debris in Jakarta Bay (2021–2024) - Santi Wilda, Marchadha; Pasaribu, Ernawati (Politeknik Statistika STIS, 2025)
Plastic waste is a critical environmental issue in Jakarta Bay, causing ecosystem degradation and challenging coastal management. This study analyzes seasonal dynamics and spatial impacts of floating plastic debris using Sentinel-2 imagery from July 2021 to November 2024. The Floating Debris Index (FDI) and Normalized Difference Vegetation Index (NDVI) were applied, with optimum thresholds determined through ROC curve analysis. Monthly median composites were processed to minimize atmospheric noise. The results show a recurring seasonal pattern, with debris consistently peaking in June, likely influenced by monsoon driven runoff and human activities. A clear increasing trend from 2021 to 2023 was followed by a decline in 2024, coinciding with the implementation of the National Ocean Love Month program. Buffer analysis indicated that most debris accumulates within 500 m of the shoreline, particularly near river mouths, ports, and settlements, while Thiessen Polygon analysis revealed hotspots concentrated along the eastern and western coasts. These findings highlight that floating plastic debris in Jakarta Bay is strongly shaped by seasonal cycles and land-based inputs, providing critical insights for designing targeted, evidence-based waste management policies.